Rancang Bangun Sistem Informasi Laporan Penjualan Heart Snack Pada PT.Flavors International - Muhamad Yusup; Meri Mayang Sari; Andri Saepudin (UNIVERSITAS RAHARJA, 2021)
In processing the cake sales report at PT Flavors Internasional still uses a manual system so that the related officers experience some problems in making sales reports. So we need a system that can handle errors in making the cake sales report which is currently still using a manual system. In this study, several methods are used including data collection which includes observation, interviews, and literature studies, the SDLC method as the analytical method used, UML is used as a tool in designing systems in the form of usecase, activity, seqeuence, and class diagrams. With this system, problems that exist in the process of making cake sales reports can be resolved properly and can provide time and process efficiency for the company, as well as more regular data report processing.